Frontiers Of Freedom: Diverse Responses to Satellite Television in The Middle East and North Africa - Sakr, Naomi (Javnost-The Public, 1999)
Satellite channels have proliferated in the Middle East and North Africa, responding to the prevalence of a shared language (Arabic), the wide extent of labour migration and the diasporisation of the Palestinian and Kurdish communities. By definition these channels are “de-terrestrialised,” but in many senses they also appear to be de-territorialised. They may be based abroad, target foreign audiences, hire foreign nationals etc. The process of receiving them enables viewers to escape from the territorial and jurisdictional confines of the countries where they live. While acknowledging that the phenomenon of deterritorialisation exists, this paper sets out to trace and locate the real power relations behind satellite broadcasting in this context. The evidence presented is divided into two parts, the first focusing on policy responses to the advent of satellite technology and the second on ways in which these responses have reconfigured the region's communicative space. The paper concludes that satellite broadcasting in the Middle East and North Africa may be deterritorialised in some aspects but is essentially driven by the exercise of political power and access to capital on the part of individuals and groups inside specific states. Thus satellite television may cross frontiers, but does not thereby bring freedom of expression.